Effect of spring grass fires on vegetation patterns and soil quality in abandoned agricultural lands at local and landscape scales in Central European Russia - Khanina, Larisa G.; Smirnov, Vadim E.; Romanov, Michael S.; Bobrovsky, Maxim V. (Ecological processes, 2018)
Introduction Abandonment of agricultural land is often happening all over the world and widespread in Russia. Such lands are subject to successional changes in vegetation and it seems necessary to provide effective methods for a sustainable ecosystem management of those lands. However, factors which determine successional processes, especially fires, have not been studied in detail. The aim of this article is to reveal how spring grass fires affect the abandoned arable lands in the study area at the landscape and local scales. Methods A region of 265.5 km 2 located in the south of Moscow was studied. At the landscape scale, we analyzed the spatial characteristics of the area in relation with a 30-year history of spring fire events extracted from the Landsat archive, and climatic data. Logistic regression was used. At the local scale, we sampled soil and vegetation at two sites and in three biotopes at each site: mature forest and two neighboring biotopes affected and unaffected by fire. Plant species diversity, soil quality, and relationship between soil and vegetation were assessed by ANOVA, v test, NMDS, and dbRDA. Results Abandoned lands covered 39% of the study area and not less than 72% of these were affected by grass fires, happening mainly between 1998 and 2014. Man causes the ignition of the field layer accidentally, but the area over which the fire spreads is determined by climatic factors and the presence of flammable material (dry grass and litter) for burning. High March temperatures and low precipitation values in April increase the inflammability of dry grasses which are abundant on the former fields. As a result, burnt areas are steadily expanding in abandoned lands where trees are scarce. On abandoned lands that were either affected or unaffected by fires, two different plant communities developed, respectively: grassy vegetation mainly dominated by Calamagrostis epigeios and young forest of pioneer trees with high crown coverage. Practically all soil variables were statistically different in three biotopes at the research sites. Plant species composition was best explained by six soil variables: P2O5, C/N, pH, K, SOC, and N values. Conclusions We showed the key role of grass fires in the formation of differences in soil and vegetation during the successional recovery of abandoned lands at the local and landscape scales.